(untitled) (Academia Journal of Medicine, 2020)
Background: Around the world dengue incidence has dramatically grown with a large number of asymptomatic cases. Worldwide about 390 million dengue infections were occurring per year, among them 96 million people were developing clinical manifestations with varied severity. About 3.9 billion people residing in 128 countries, were at-risk of dengue virus infection. Dengue fever (DF) is one of the common causes of acute febrile illness. In half the patients with dengue fever skin involvement occurs. The aim of the study is to study the socio-demographic parameters, clinical features and laboratory parameters among the patients with and without skin rash in dengue infection. Also determine outcome among the patients with dengue fever and its association with skin rash. Subjects and Methods: A hospital-based, analytical prospective study was conducted in the Department of General Medicine, Sapthagiri Institute of Medical Sciences and Research Center, Bangalore. Patients older than 16 years of age with clinical features and laboratory reports suggestive of dengue infection were included. The study was conducted for a period of 12 months from 1st December 2014 to 30th November 2015. These patients were further divided based on the skin rash presence and absence. The data obtained was entered in Microsoft Excel and analyzed in SPSS version-22 trial. Analysis was done using unpaired students t-test, ANOVA. Results: In total 97 patients with dengue fever were enrolled into the study. About 14.4 p.c (14) patients were with skin rash. The patients with skin rash were found to have lower platelet levels during the disease course. Patients with skin rash had higher percentage of platelet transfusion which was statistically significant. Conclusion: A cutaneous involvement may facilitate clinical diagnosis but it may not be present among all the patients.